ANALISIS RESEPSI PENGGUNAAN MEDIA SOSIAL UNTUK PENGAMBILAN KEPUTUSAN PADA KAMPANYE NEW NORMAL - Eravany Noura Widyanggari (Jurnal Komunikasi dan Budaya, 2021)
The decline in the spread of the Covid-19 Virus in May 2020 has provided a "fresh air" for people to start activities with a new life order (new normal). This step began with President Jokowi's visit to a mall in Bekasi and was followed by the delivery of health protocol information by the Covid-19 Task Force Communications Team on one of the Youtube social media "Tips to Prevent Corona in the Mall Ala Dokter Reisa". The purpose of this study was to determine the public's acceptance of the video, the decisions that the community would take after watching the video and whether the speaker had an effect on receiving information. The method in this study uses reception analysis from 10 informants with a productive age range of 25 - 34 years and refers to the theory of decision making by George R. Terry and Brinckloe. The results showed that not all informants agreed with the information presented or entered the Negotiated Reading category. 90% made the decision would go to the mall with health protocols implementation. This decision is based on Fact and Logic or Rationality. The community does not pay too much attention to the figure of the information provider but rather the information provided and still follows instructions given for health reasons.